The Impact of Narrow Reading on Enhancing English Vocabulary among University Students: Dampak Narrow Reading terhadap Peningkatan Kosakata Bahasa Inggris di Kalangan Mahasiswa Universitas - Lailiy Kurnia; Budyi Suswanto (Nusantara Journal of Multidisciplinary Science, 2024)
Previous research on reading has indicated that the primary obstacle for university students in understanding texts is often unfamiliar vocabulary. This study aims to examine the effectiveness of narrow reading in enhancing the vocabulary of university students and to assess their perceptions of this strategy's implementation. The research design utilised was pre-experimental. The study included 25 second-semester Management majors at a university. Data collection instruments consisted of vocabulary tests and a questionnaire, and the data was analysed using IBM SPSS Statistics 25. The results indicate that narrow reading is an effective strategy for improving the vocabulary of university students. The statistical analysis revealed a significant improvement in students' vocabulary achievement after the implementation of narrow reading (p = 0.000, which is less than 0.05). In conclusion, the narrow reading strategy has been shown to enhance the vocabulary comprehension of university students effectively. Furthermore, the students have a positive perception of the implementation of the narrow reading strategy. It is recommended that English instructors consider incorporating narrow reading into their teaching practices, and future researchers can use these findings as a reference.